2016
DOI: 10.1038/ismej.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

A genomic comparison of 13 symbiotic Vibrio fischeri isolates from the perspective of their host source and colonization behavior

Abstract: Newly hatched Euprymna scolopes squid obtain their specific light-organ symbionts from an array of Vibrio (Allivibrio) fischeri strains present in their environment. Two genetically distinct populations of this squid species have been identified, one in Kaneohe Bay (KB), and another in Maunaloa Bay (MB), Oahu. We asked whether symbionts isolated from squid in each of these populations outcompete isolates from the other population in mixed-infection experiments. No relationship was found between a strain's host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 64 publications
4
86
0
Order By: Relevance
“…2), or to the ratio of strains within the aggregate (Supporting Information Fig. S1) (Bongrand et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2), or to the ratio of strains within the aggregate (Supporting Information Fig. S1) (Bongrand et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Horizontal transmission also impacts the genetic features of the symbiont cells. For example, in model associations, such as the legume–rhizobia symbioses, specificity can be influenced by antagonistic interactions occurring between different combinations of host and symbiont genotypes, or between strains of the same symbiont species within a given host (Pellmyr and Huth, ; Frank, ; Kiers et al ., ; Sachs et al ., , Poulsen and Boomsma, ; Bongrand et al ., ). A recent study of the model symbiosis between Steinernema nematodes and Xenorhabdus bovienii (Murfin et al ., ) showed that strain‐level differences in the fitness benefits of microbial symbionts drive variation in the success of host–microbe associations, likely contributing to the maintenance of symbiotic associations over evolutionary time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, host‐mediated factors along with abiotic variables such as water temperature and salinity have been known to shape these mutualist assemblages (McFall‐Ngai, 2014; McFall‐Ngai et al., 2012; Nishiguchi, 2000; Soto, Gutierrez, Remmenga & Nishiguchi, 2009). Collectively, either genomic comparison of closely related populations (Bongrand et al., 2016) or haplotype comparisons of allopatric populations of Indo‐west Pacific squid and their vibrio symbionts (Jones et al., 2006) do not address the connectivity of populations across physical and biogeographic barriers like those in the Philippines or across the IPB. Therefore, we examined the genetic architecture of Euprymna albatrossae (Cephalopoda: Sepiolidae) and their V. fischeri symbionts in the Philippine archipelago using a combined phylogeographic approach to determine whether host specificity or geographic location influence the distribution of symbiotic Vibrios in this region.…”
Section: Introductionmentioning
confidence: 99%